Implications of Empiricism Theory in the Development of Professionalism Among Elementary School Teachers - Budiono, Hendra; Fitrah, Yundi; Kusmana, Ade; Wulandari, Bunga Ayu (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2024)
This research aims to describe the implications of empiricism theory in the development of professionalism among elementary school teachers. This study is qualitative and employs a literature review method. The research seeks sources related to the empiricism movement concerning the development of professionalism among elementary school teachers. The sources for this research include books, research articles, and other supporting documents. The results of this study indicate that the empiricism movement brings a different nuance to the world of education in developing the professionalism of teachers, especially in elementary schools. This movement provides a foundation of responsibility for teachers regarding the nature of every learning practice in elementary schools through their senses. Thus, it fosters a good and accurate understanding of the needs of students, and it is hoped that students will acquire knowledge based on their experiences. The perspective of empiricism in the development of teacher professionalism also provides direction and fundamental guidelines for efforts to improve, advance, and establish a solid foundation for maintaining education.